Kemampuan Berbahasa Indonesia Siswa Sekolah Dasar Kelas VI di Kota Jayapura - Normawati Normawati (Balai Bahasa Provinsi Papua, 2019)
Positive attitude is the first priority on Indonesian learning that must have grown firstly. It goal is to set better Indonesian role in public education. It is showing that language education must get attention since elementary level then to be contunued and develop until the higher education level.On this simple paper is drawing the using ability of Indonesian of Elementary School students on five year in Jayapura. It correlate by school location, central or urban city, school state, sex, and their job's parents background.